BF3‐Catalyzed Mukaiyama aldol reaction of acetaldehyde with 2‐siloxy‐1‐propene. Issue 6 (21st December 2021) - Li, Xuening; Li, Ying; Sun, Yuanyuan; Meng, Lingpeng; Zeng, Yanli
Abstract: The Mukaiyama aldol reaction is a powerful tool for the construction of the carbon–carbon bond and the formation of β‐hydroxycarbonyl compounds. In this work, the mechanism of acetaldehyde and 2‐siloxy‐1‐propene both in the absence and presence of the catalyst BF3 was investigated based on density functional theory. The mechanism includes two major steps: the formation of the carbon–carbon bond and the removal of SiH3 /BF2 by water. The energy barrier of the carbon–carbon bond formation process in the presence of BF3 is obviously lower, indicating that BF3 is a good catalyst for this reaction. In terms of molecular configuration, the different tensions between the five‐membered‐ring and six‐membered‐ring can be considered as the possible reason for the catalytic effect of BF3 . In terms of charge transfer, the charges of natural population analysis in the carbon atom of the carbonyl group in acetaldehyde becomes more positive, which is easier to attack by nucleophiles and promote the nucleophilic process. Abstract : The catalysis mechanism of BF3 on the Mukaiyama aldol reaction was investigated using the density function theory. The results show better catalytic performance in the carbon–carbon coupling process which activate the carbonyl group to accelerate the reaction by the formed boron bonds.